Arithmetic of finite fields : 5th International Workshop, WAIFI 2014, Gebze, Turkey, September 27-28, 2014. Revised selected papers /: 5th International Workshop, WAIFI 2014, Gebze, Turkey, September 27-28, 2014. Revised selected papers. (2015) - Unknown
No abstract available